The Role of the Intelligence Unit in Intelligence Investigation in Disclosing Motor Vehicle Theft Cases to Create a Conducive Kamtibmas at Pekalongan Police - Jaladhira Satya, Kevin (Advances in Police Science Research Journal, 2024)
Disclosure of theft cases at the Pekalongan Police only reached half of what it should have been. This is caused by the less than optimal role of Intelligence unit, indicating that there are serious problems in handling crime cases at the Pekalongan Police. Intelligence unit has a very important role in gathering intelligence information to assist law enforcement and uncover crimes. This study aims to describe the crime of motor vehicle theft, the factors that influence intelligence investigations and the role of intelligence investigations carried out in uncovering criminal acts of motor vehicle theft in the context of investigation purposes at the Pekalongan Police. The author chose a qualitative approach in writing this because this method allows the writer to make direct observations and interviews with research subjects, thus enabling the writer to obtain more in-depth data and is rich in information. In addition, a qualitative approach allows writers to understand complex and multifaceted social phenomena from a broader perspective and pay attention to a wider context. Qualitative methods can also help writers to dig up additional information that is not measurable or difficult to measure with quantitative methods. Based on the results of interviews, observations, and data processing at the Intelligence unit Polres Pekalongan, it was found that there was a shortage of human resources, no personnel to carry out education and training, lack of discipline in the Intelligence unit administration in disclosing theft cases and synergy with related functions and lack of supervision. Based on the results of the study it was concluded that why the disclosure of theft was not more than half due to the suboptimal role of Intelligence unit in disclosing theft cases in the form of a lack of administrative discipline and synergy between functions which resulted in no follow-up on the results of intelligence investigations in the disclosure of theft cases. So the Intelligence unit Polres Pekalongan needs to optimize the role of the Intelligence unit in disclosing cases of theft at the Pekalongan Police.